Effects of lean practices and knowledge sharing on performance of food manufacturers - Repin@Rebin, Muhamad Fadzil (2022)
The new concept of food manufacturing performance focuses on consumer preferences and needs, high quality packaging and branding system, efficient logistics and procurement, high value-added products and lower operating costs. Research on manufacturing performance has received much attention with contradictory findings. However, research on measuring lean practices that affect manufacturing performance, especially in food manufacturing, has received little attention. The lean practices concept, such as the right product is at the right time and location Just-in-time (JIT), waste reduction (Elimination of Waste) and continuous improvement (Kaizen) can affect manufacturing performance. Products and services are always expected to be derived on time to ensure low-cost production and flexibility, by reducing non-value-adding operations or “waste” while fulfilling customers’ needs. Based on the literature reviewed, it was found that there are four important indicators of manufacturing performance: flexibility, responsiveness, customer satisfaction, and cost. Knowledge sharing (KS) can be considered as an essential platform to align activities and share information on joint performance measurement within the supply chain. KS have become a major driver of competitive advantage and important contribution to the support of core and supporting activities of industries. This thesis presents a review of literature with the aim of developing a conceptual framework and the findings on the relationship between lean practices, knowledge sharing and manufacturing performance factors. Specifically, the objectives were to develop a framework to link lean practices and manufacturing performance based on the literature reviewed, explore the relationship between lean practices and manufacturing performance and to empirically test whether knowledge sharing mediates the relationship between lean practices and manufacturing performance. The survey was conducted through face-to-face interview and e-mail correspondence. There was 282 companies involved as the respondents of the study. The Confirmatory Factor Analysis (CFA) and Structural Equation Modeling (SEM) were performed to test the construct validity or to “confirm” the construct and to test model fits. The findings validated the significant effects of manufacturing lean practices on manufacturing performances in Malaysia’s food manufacturing companies on all variables. However, the mediating effect on knowledge sharing was confirmed as not significant. Knowledge sharing was proven to not mediate the relationship between lean practices and manufacturing performance, but lean practices had a positive and significant effect on knowledge sharing. The finding also showed that training and sharing value as the two sub-constructs of knowledge sharing to be emphasized the most, while trust and communication as the least important but significant between the food manufacturers in Malaysia. However, this research investigated only the relationship between several dimensions of lean practices and knowledge sharing. Further research should extend into relevant theoretical constructs and other elements and activities in practice such as the association between sustainability and the manufacturing environment and technological capabilities, including more refined measurement for the constructs to better capture the current situation in manufacturing industry.